Frequency of odontomas in pediatric patients treated at a dental teaching healthcare clinic between the years 2015-2018 Lima - Perú. Retrospective study - Corral - Peñafiel, David Francisco (2020)
Objectives: To determine the frequency of odontomas through digital panoramic radiographs in pediatric pa-tients treated at the Dental Teaching Assistance Center of the Universidad Peruana Cayetano Heredia during the period 2015-2018.Material and methods: The present study is descriptive, cross-sectional, and retrospective with a total of 2707 digital panoramic radiographs of pediatric patients from 3 to 17 years old taken at the Dental Teaching Assistance Center of the Universidad Peruana Cayetano Heredia during the period 2015 - 2018. Results: A total of 34 odontomas (1.26%) were found, of which 53.60% (n = 20) were female and 46.40% (n = 14) were male, The most frequent condition according dental age was in the permanent dentition with 41.18%(n = 14). The compound odontoma was the most frequent entity with 52.94% (n = 18), and both entities were located in the anterior superior anatomical area, which is the most common with 64.71% (n = 22).Conclusions: The odontoma had a low frequency in pediatric patients in the Dental Teaching Assistance Center of the Universidad Peruana Cayetano Heredia during the period 2015-2018.